2017
DOI: 10.1016/j.nano.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor accumulation of liposomal doxorubicin in three murine models: Optimizing delivery efficiency

Abstract: Systemic drug delivery to a solid tumor involves a sequence of steps that determine efficacy and survival. Extravasation from circulation at the tumor site is a critical step in this sequence since it regulates how much of the drug accumulates in the tumor. Despite its importance in determining outcomes, extravasation from circulation remains a “black box.” The objective of this study is to develop predictive tools for optimization of drug delivery systems. By comparing pharmacokinetics of liposomal doxorubici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Hence, it is a common model drug for constructing drug delivery vehicles. Several studies have shown Dox loading to different carriers such as liposomes, polymeric nanoparticles, nanomicelles, and others . However, to the best of our knowledge, there is a lack of reports on the use of RuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is a common model drug for constructing drug delivery vehicles. Several studies have shown Dox loading to different carriers such as liposomes, polymeric nanoparticles, nanomicelles, and others . However, to the best of our knowledge, there is a lack of reports on the use of RuNPs.…”
Section: Discussionmentioning
confidence: 99%
“… 23 By contrast, the LTLD formulation that we used in this trial is understood to act by rapid diffusion of doxorubicin into the tumour interstitium under conditions of mild hyperthermia, with only a small proportion of doxorubicin entering the tumour by enhanced permeability and retention. These intended delivery mechanisms are reflected in the circulation profiles of the two formulations, with NTLD having a half-life of more than 10 h while LTLD has a shorter half-life of about 1 h. 9 , 10 , 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Regardless, some general trends could be observed for factors leading to poorly fitted data, such as when the plasma particle concentrations reported were consistently lower than tumor values [5557]: a puzzling scenario considering that systemically-administered particles ought to have the highest concentration in the blood pool before being distributed to various organs. The tumor concentration values may also have high variability with no observable trend with respect to time [58,59], or achieved high levels within an hour and appear to plateau despite particle clearance from the bloodstream [6062], which may indicate lasting retention in the tumors (see examples in Supplementary Information). Some of these cases may have arisen from differences in methods employed for measuring particle concentration in the blood and tumor (e.g.…”
Section: Resultsmentioning
confidence: 99%